2015
DOI: 10.1016/j.antiviral.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The use of nonhuman primates in research on seasonal, pandemic and avian influenza, 1893–2014

Abstract: Attempts to reproduce the features of human influenza in laboratory animals date from the early 1890s, when Richard Pfeiffer inoculated apes with bacteria recovered from influenza patients and produced a mild respiratory illness. Numerous studies employing nonhuman primates (NHPs) were performed during the 1918 pandemic and the following decade. Most used bacterial preparations to infect animals, but some sought a filterable agent for the disease. Since the viral etiology of influenza was established in the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 222 publications
0
43
0
Order By: Relevance
“…The experimental infection of macaques with FLUAV results in viral spread and influenza symptoms, which are usually not as pronounced as those observed in human influenza patients [29,30]. Nevertheless, infection of macaques with highly pathogenic FLUAV, the pandemic H1N1 virus of 1918 and H5N1 avian influenza viruses, induces severe disease and the macaque model has been successfully used for vaccine-, treatment-and pathogenesis-studies [31][32][33]. Based on these studies, it has been suggested that the macaque model mirrors human physiology, development of pneumonia as well as cytokine and chemokine responses more closely than other animal models (mice, ferrets) [34].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental infection of macaques with FLUAV results in viral spread and influenza symptoms, which are usually not as pronounced as those observed in human influenza patients [29,30]. Nevertheless, infection of macaques with highly pathogenic FLUAV, the pandemic H1N1 virus of 1918 and H5N1 avian influenza viruses, induces severe disease and the macaque model has been successfully used for vaccine-, treatment-and pathogenesis-studies [31][32][33]. Based on these studies, it has been suggested that the macaque model mirrors human physiology, development of pneumonia as well as cytokine and chemokine responses more closely than other animal models (mice, ferrets) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Influenza viruses cause recurrent seasonal epidemics or pandemics of respiratory infection that lead to 3 million to 5 million cases of severe illness and 250,000 to 500,000 deaths worldwide every year 1,2 . Especially in infants, young children, pregnant women, the elderly, and patients with weakened immune systems, influenza is likely to cause serious complications; therefore, the World Health Organization (WHO) has identified influenza as a major public health problem 3,4 .…”
mentioning
confidence: 99%
“…onhuman primates (NHP) play an important role as animal models for influenza virus research (1,2). Novel candidate influenza vaccines are commonly tested for safety and efficacy in mice and ferrets and/or macaques before they are evaluated for immunogenicity in humans (2,3).…”
mentioning
confidence: 99%
“…Novel candidate influenza vaccines are commonly tested for safety and efficacy in mice and ferrets and/or macaques before they are evaluated for immunogenicity in humans (2,3). However, whereas for mice and ferrets dose-finding studies have been described and implemented for testing of vaccines and antiviral agents (4)(5)(6)(7)(8)(9)(10)(11), for macaques usually a standard challenge dose is used, typically in the range between 10 6 and 10 7 50% tissue culture infective doses (TCID 50 ) (12)(13)(14)(15).…”
mentioning
confidence: 99%